2017
DOI: 10.1007/s00125-016-4196-9
|View full text |Cite
|
Sign up to set email alerts
|

Low muscle mass and risk of type 2 diabetes in middle-aged and older adults: findings from the KoGES

Abstract: Aims/hypothesis Asians have a propensity to develop type 2 diabetes with a lower BMI than Western populations. This discrepancy may be due to differences in body fat and muscle mass for a given BMI. However, unlike adiposity, it is unclear whether muscle mass affects the risk of type 2 diabetes in Asian populations. Methods We conducted a 2-yearly prospective assessment of 6895 participants who were free of diabetes at the baseline examination as part of the Korean Genome Epidemiology Study. The muscle mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 36 publications
7
137
2
1
Order By: Relevance
“…However, we showed that Cre/(CysC × BW) is associ- [8,[25][26][27]. In fact, weight-adjusted SMI is reported to be associated with incident diabetes [8], incident metabolic syndrome [28] and progression of NAFLD [29]. In this study, we used absolute muscle mass as numerator of formula of weightadjusted SMI.…”
Section: Discussionmentioning
confidence: 98%
“…However, we showed that Cre/(CysC × BW) is associ- [8,[25][26][27]. In fact, weight-adjusted SMI is reported to be associated with incident diabetes [8], incident metabolic syndrome [28] and progression of NAFLD [29]. In this study, we used absolute muscle mass as numerator of formula of weightadjusted SMI.…”
Section: Discussionmentioning
confidence: 98%
“…T2D and muscle atrophy develop hand in hand, and it has previously been speculated that muscle loss might be a cause as well as a consequence of T2D. Studies suggesting a causal role for muscle loss in the development of metabolic disturbances are relatively scarce though, and to our knowledge, there is only one study that evaluated the association between low muscle mass and incidence of T2D in a longitudinal manner . Specifically, Son et al followed 6895 participants from Asian descent for a period of approximately 9 years and observed an inverse association between muscle mass index and the development of T2D.…”
Section: Muscle Loss In Individuals With T2d: Cause or Consequence?mentioning
confidence: 99%
“…Main covariates included age, sex, urban or rural residence, family history of diabetes, hypertension, smoking status, education level, monthly income, physical activity, alcohol consumption, and diet. Also, additional adjustments for body fat mass, waist circumference, and body mass index (BMI) did not modify the relationship . The assumption that muscle loss may play a causal role in the development of T2D is partly based on the fact that skeletal muscle is a major determinant of total energy expenditure .…”
Section: Muscle Loss In Individuals With T2d: Cause or Consequence?mentioning
confidence: 99%
“…Thus, decreased skeletal muscle mass could potentially trigger insulin resistance, which is an underlying mechanism of diabetes. Two cohort studies from Korea have shown that low muscle mass, defined using relative muscle mass and muscle mass index (appendicular), respectively, is linked with a greater risk of incident diabetes in both young and old people.…”
Section: Introductionmentioning
confidence: 99%